2010
DOI: 10.1111/j.1365-2567.2009.03179.x
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor‐induced innate immune responses in non‐parenchymal liver cells are cell type‐specific

Abstract: Summary Little is known of how the Toll‐like receptor (TLR) system can modulate the function of non‐parenchymal liver cells (NPC) as a major component of the innate and adaptive immune system of the liver. To investigate the diversification of TLR signalling pathways in NPC, we isolated Kupffer cells (KC) and liver sinusoidal endothelial cells (LSEC) from wild‐type C57BL/6 mice and examined their responses to TLR1 to TLR9 agonists. The data show that KC respond to all TLR ligands by producing tumour necrosis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
176
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(189 citation statements)
references
References 36 publications
9
176
0
1
Order By: Relevance
“…In our study, a high dose of poly(I:C) (50 g) failed to achieve better antiviral effects than the intermediate dose of 20 g. We have previously shown that the poly(I:C) stimulation of innate immune responses in LSEC and Kupffer cells is dose dependent: high levels of cytokine production and allogeneic T-cell proliferation were found at a dose of 100 g/ml but not at the higher dose of 200 g/ml (26). Other studies have suggested that an excessive amount of poly(I:C) may produce a response spectrum unsuitable for viral clearance, such as transactivating p63 (Tap63␣)-dependent apoptosis (27), activation of intracellular negative regulatory molecules, including A20, tumor necrosis factor-related apoptosis-inducing ligand receptor (TRAIL-R), and ubiquitin 1 (28); and type I IFN-dependent exhaustion of memory T cells (29,30) and dendritic cells (DCs) (31).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a high dose of poly(I:C) (50 g) failed to achieve better antiviral effects than the intermediate dose of 20 g. We have previously shown that the poly(I:C) stimulation of innate immune responses in LSEC and Kupffer cells is dose dependent: high levels of cytokine production and allogeneic T-cell proliferation were found at a dose of 100 g/ml but not at the higher dose of 200 g/ml (26). Other studies have suggested that an excessive amount of poly(I:C) may produce a response spectrum unsuitable for viral clearance, such as transactivating p63 (Tap63␣)-dependent apoptosis (27), activation of intracellular negative regulatory molecules, including A20, tumor necrosis factor-related apoptosis-inducing ligand receptor (TRAIL-R), and ubiquitin 1 (28); and type I IFN-dependent exhaustion of memory T cells (29,30) and dendritic cells (DCs) (31).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HBV also evolves to counteract the host innate defense system. The TLR-mediated antiviral activity, for example, was inhibited by HBV (33). Recently, HBV pol and X protein (HBx) were shown to modulate innate immune signaling (16,29,30,36).…”
Section: Discussionmentioning
confidence: 99%
“…The inability of hepatocytes to respond to IFN-I could be explained by the finding that hepatocytes failed to express significant levels of messenger RNA encoding IFNAR and downstream signaling molecules compared with macrophages. Liver endothelial cells are equipped with Toll-like receptors and are involved in the antiviral innate immune response, 34,35 including uptake of serum particles. 15 In addition to cytokine production, liver sinusoid endothelial cells show a strong antiviral response to IFN-I, 34,36 which could suppress virus replication 37 ; however, whether this is of benefit for a systemic virus infection remains to be studied.…”
Section: Discussionmentioning
confidence: 99%